Evaluation of Chemical Composition, Essential Oil and Morphological Traits in Wild Populations of Lavandula stoechas L. in the Mediterranean Environment - Arabaci, Olcay; Bayram, Emine (Asian Journal of Chemistry, 2010)
The morphological traits, essential oil compositions and the relationship among 25 populations of Lavandula stoechas L. from different locations in the west part of Turkey were determined. Twenty-five Lavandula stoechas L. populations varied between 16.71 to 32.90 mm for flower spike length, 6.70 to 11.04 mm for flower spike width, 0.84 to 2.83 g for flower spike weight and 0.39 to 2.04% essential oil contents. Results indicated that the variability of the morphological characters, essential oil content and essential oil composition in different populations of the Lavandula stoechas L. would be attributed to genetic diversity. Comparing the essential oil content among different populations, there is a negative correlation between morphological characters (flower spike weight) and essential oil content and a positive correlation between altitudes of population growing location and essential oil. Eleven essential oil components were identified in Lavandula stoechas L. populations. All populations were characterized as 1,8-cineole/camphor chemo type.